1998
DOI: 10.1091/mbc.9.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Signal Recognition Particle-dependent Targeting of Ribosomes to the Rough Endoplasmic Reticulum in the Absence and Presence of the Nascent Polypeptide-associated Complex

Abstract: Proteins with RER-specific signal sequences are cotranslationally translocated across the rough endoplasmic reticulum through a proteinaceous channel composed of oligomers of the Sec61 complex. The Sec61 complex also binds ribosomes with high affinity. The dual function of the Sec61 complex necessitates a mechanism to prevent signal sequenceindependent binding of ribosomes to the translocation channel. We have examined the hypothesis that the signal recognition particle (SRP) and the nascent polypeptide-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 45 publications
5
53
1
Order By: Relevance
“…These RNCs could bind to RMs that were stripped of ribosomes by puromycin/high salt treatment (PK-RMs; Supplemental Figure 1A). As reported previously, the preincubation of PK-RMs with an excess of nontranslating ribosomes significantly reduced RNC binding, unless SRP was present (Supplemental Figure 1A; Neuhof et al, 1998;Raden and Gilmore, 1998). Similar results were obtained with proteoliposomes containing purified Sec61 complex and SR (Supplemental Figure 1B; Neuhof et al, 1998).…”
Section: Testing the Membrane Dissociation Of Prebound Ribosomessupporting
confidence: 84%
See 2 more Smart Citations
“…These RNCs could bind to RMs that were stripped of ribosomes by puromycin/high salt treatment (PK-RMs; Supplemental Figure 1A). As reported previously, the preincubation of PK-RMs with an excess of nontranslating ribosomes significantly reduced RNC binding, unless SRP was present (Supplemental Figure 1A; Neuhof et al, 1998;Raden and Gilmore, 1998). Similar results were obtained with proteoliposomes containing purified Sec61 complex and SR (Supplemental Figure 1B; Neuhof et al, 1998).…”
Section: Testing the Membrane Dissociation Of Prebound Ribosomessupporting
confidence: 84%
“…The occupation of ribosome binding sites raises the question of how ribosomes that carry nascent chains destined for translocation can efficiently be targeted to Sec61. Experiments in vitro have shown that SRP is required for the binding of RNCs in the presence, but not absence, of competing ribosomes (Neuhof et al, 1998;Raden and Gilmore, 1998). SRP promotes RNC targeting both when competing ribosomes are present during the binding reaction and when they are prebound to the membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively NAC might modulate the interaction of SRP with the ribosome (Powers and Walter, 1996) or the interaction of RNCs with the ER (Lauring et al, 1995a,b;Mö ller et al, 1998). The latter finding has been challenged (Neuhof et al, 1998;Raden and Gilmore, 1998). Recent experiments describe yeast NAC as a ribosome-associated complex involved in mitochondrial protein import and possibly targeting to the ER (George et al, 1998).…”
Section: Purification Of Nac As An Import Stimulatory Factormentioning
confidence: 99%
“…Adding back purified NAC to the system restored the fidelity of cotranslational ribosome binding and translocation of only secretory polypeptides (10). Recently the function of NAC in ribosome targeting to the ER was questioned (11,12) in studies that used subphysiological concentrations of NAC. Although we were able to reproduce these results, we found that, when NAC was restored to physiological levels, our original observations were confirmed (1).…”
mentioning
confidence: 99%